How a speech therapist can help children with selective mutism? - Marciniak-Firadza, Renata (Selected issues from the theory and practice of speech therapy, 2018)
The need to communicate with others is one of the most important mental needs of people. Children with selective mutism want to communicate with others but they are unable to do it. Selective mutism is the condition that does not disappear spontaneously, therefore it is necessary to provide children and their families with the therapeutic treatment as early as possible. The most important thing to do is to increase self-confidence of children, among others by trying to help them overcome their fear of verbal contact or any other anxiety that makes that contact difficult. There is no single therapeutic strategy or procedure in the treatment of children with selective mutism because of the specificity of this condition and its complex etiology.